Application-Based Development of Alternative and Augmentative Communication System for Children with Cerebral Palsy - Lamina Amalia Putri; Diana Shanty; Oom Sitti Homdijah; Rizki Ramadhan; Rahardian Sakti (research, training and philanthropy institution Natural Aceh, 2023)
Based on the observation results, children with cerebral palsy were the subjects of the study. They communicate using gestures such as pointing accompanied by meaningless vocalizations. Only some people can immediately understand what the child intends. When they need something, the child will cry and scream. Based on these obstacles, the children need media as an alternative and augmentative communication system that can support them in communicating with their modalities and needs, one of which is using symbolic pictures and voice output. This research aims to design an alternative and augmentative communication program based on the children's assessment results. This research uses a qualitative approach with data collection techniques such as interviews, observations, and documentation. The study results in a program design expected to be implemented as a comprehensive tool to assist children in communication.